2020
DOI: 10.1139/cjm-2019-0393
|View full text |Cite
|
Sign up to set email alerts
|

Insights into irr and rirA gene regulation on the virulence of Brucella melitensis M5-90

Abstract: Iron is a fundamental element required by most organisms, including Brucella. Several researchers have suggested that the iron response regulator (irr) and rhizobial iron regulator (rirA) genes regulate iron acquisition by Brucella abortus, influencing heme synthesis by and virulence of this pathogen. However, little is known about another Brucella species, Brucella melitensis. In this research, we successfully constructed two mutants: M5-90Δirr and M5-90ΔrirA. The adhesion, invasion, and intracellular surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Additionally, the iron uptake system also plays a role in the virulence of Brucella and pseudomonas aeruginosa . Mutation of the iron uptake system leads to the attenuation or even an avirulent phenotype both in vitro and in vivo ( 30 , 31 ). Results of KEGG database analysis in our study indicate that the Brucella Zur protein (encoded by gene BMEII0175 , protein accession: Q8YDK0) is indirectly associated with iron uptake and this protein is over-represented in the Y3 strain ( Table S3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the iron uptake system also plays a role in the virulence of Brucella and pseudomonas aeruginosa . Mutation of the iron uptake system leads to the attenuation or even an avirulent phenotype both in vitro and in vivo ( 30 , 31 ). Results of KEGG database analysis in our study indicate that the Brucella Zur protein (encoded by gene BMEII0175 , protein accession: Q8YDK0) is indirectly associated with iron uptake and this protein is over-represented in the Y3 strain ( Table S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results of KEGG database analysis in our study indicate that the Brucella Zur protein (encoded by gene BMEII0175 , protein accession: Q8YDK0) is indirectly associated with iron uptake and this protein is over-represented in the Y3 strain ( Table S3 ). In addition to the Irr and RirA proteins that are involved in iron transport in Brucella ( 31 ), Zur might be another regulatory protein involved in Brucella iron metabolism. It has been discovered that ABC transporters are crucial virulence factors in Streptococcus pneumoniae and Escherichia coli ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research focused on identification of B. melitensis M5-90 virulence factors ( Li et al, 2015 ; Zhang et al, 2020 , 2017 ) and elucidating unique gene expression profile of mouse infected macrophages ( Wang et al, 2011b ; Xu et al, 2021 ). In macrophages, it has already been observed that the two-component system BvrR/BvrS of B. meliten sis is required to modulate bacterial physiology and the shift from extracellular to intracellular life ( Martín-Martín et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The viability of A19ΔvirB and parental strain A19 was assessed in Murine macrophage RAW264.7 and Murine dendritic cell sarcoma (DCS), as previously described (Zhang et al 2020). Briefly, macrophages and dendritic cells of 1×10 6 cells/well were inoculated into 6-well plates for 24 h in a cell culture incubator containing 5% CO2 at 37° C and then infected with brucella abortus A19 and mutated brucella abortus A19 at a multiplicity of infection (MOI) of 100:1.…”
Section: Evaluation Of A19δvirb Attenuation In Raw2647 Macrophages and Murine Dendritic Cell Sarcomamentioning
confidence: 99%
“…However, the detection of antibodies in mouse serum was carried out by the method described by Zhang (Zhang et al 2020), and the Recombinant VirB1, VirB5, VirB8 and L7/L12 were used as detection proteins, and antibodies against VirB1, VirB5, VirB8 and L7/L12 were detected by Western blot.…”
Section: Western Blottingmentioning
confidence: 99%